Nilai-Nilai Pendidikan Karakter Religius dalam Novel Assalamualaikum Calon Imam Karya Ima Madaniah - Cahyaning Azami Fahmi; Sri Haryanto; Ali Imron (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Religious character education is an effort to approach education aimed at shaping the attitudes and behaviors of students in accordance with the principles of their faith. This study aims to describe the values of religious character education found in the novel